Engineering exosomes and exosome-like nanovesicles for improving tissue targeting and retention - Lanya Li; Fei Wang; Dashuai Zhu; Shiqi Hu; Ke Cheng; Zhenhua Li (Fundamental Research)
Exosomes are natural nano-size particles secreted by human cells, containing numerous bioactive cargos. Serving as crucial mediators of intercellular communication, exosomes are involved in many physiological and pathological processes, such as inflammation, tissue injury, cardiovascular diseases, tumorigenesis and tumor development. Exosomes have exhibited promising results in the diagnosis and treatment of cancer, cardiovascular diseases and others. They are a rapidly growing class of drug delivery vehicles with many advantages over conventional synthetic carriers. Exosomes used in therapeutic applications encounter several challenges, such as the lack of tissue targeting capabilities and short residence time. In this review, we discuss recent advances in exosome engineering to improve tissue targeting and describe the current types of engineered exosome-like nanovesicles, and summarize their preclinical applications in the treatment of diseases. Further, we also highlight the latest engineering strategies developed to extend exosomes retention time in vivo and exosome-like nanovesicles.